Imaging synaptic plasticity - Padamsey Zahid; Emptage Nigel J (Molecular Brain, 2011)
Abstract Over the past decade, the use and development of optical imaging techniques has advanced our understanding of synaptic plasticity by offering the spatial and temporal resolution necessary to examine long-term changes at individual synapses. Here, we review the use of these techniques in recent studies of synaptic plasticity and, in particular, long-term potentiation in the hippocampus.